Agency: What Does It Mean to Be a Human Being? - Williams, Richard N.; Gantt, Edwin E.; Fischer, Lane (Frontiers in Psychology, 2021)
This paper will look at results of what has been termed “the crisis of modernism” and the related rise of postmodern perspectives in the 19th and 20th centuries. It concentrates on what is arguably the chief casualty of this crisis – human agency – and the social science that has developed out of the crisis. We argue that modern and postmodern social science ultimately obviates human agency in the understanding of what it means to be a human being. Attention is given to the contemporary intellectual world and the way in which it has been deeply informed by neo-Hegelian and other postmodern scholarly trends, particularly in accounting for how agency has come to play little role in social science understanding of human action. The paper also offers an alternative conception of human agency to the commonly endorsed libertarian model of free choice. Finally, the paper argues that this view of agency preserves meaning and purpose in human action and counters the pervasive social science worldview that sacrifices agency and meaning to powerful invisible abstractions.